From conflict early warning to fostering resilience? Chasing convergence in EU foreign policy. Issue 7 (3rd October 2021) - Bressan, Sarah; Bergmaier, Aurora
ABSTRACT: To prevent violent conflict and governance breakdown abroad, the European Union (EU) needs anticipatory analysis and preventive action at the EU and member state level that follow a coherent approach. The EU's resilience agenda can complement early warning risk analysis for prevention, but it is unclear to what extent it has been operationalized. We compare the role that resilience plays in crisis early warning in diplomatic services at the EU and member state level in France and Germany. Drawing on the literature on Europeanization and diffusion, we seek to explain different levels of convergence regarding a resilience approach in early warning at the levels of strategy, analysis and action. We find that the diffusion item's specificity, the number of sources and particular institutional contexts impact the resulting level of convergence. Member states see value in complementing risk analysis with a resilience perspective, but the EU has failed to provide a sufficiently clear source model. Our results contribute to the literature on EU foreign policy diffusion and coherence and show that the EU has not exhausted its potential to promote resilience as a tool for more coherent and effective conflict prevention.